Macrosomía Fetal por Diabetes Gestacional - Velásquez Litardo, Yomira Lisbeth (2020)
Gestational diabetes is diagnosed between week 24 and 28 of pregnancy, it is related to unfavorable consequences for the mother, the fetus and the newborn. The objective of the presentation of the clinical case on fetal macrosomia due to gestational diabetes is to evaluate compliance with protocols for the care of Gestational Diabetes for the prevention of fetal complications related to macrosomia according to the clinical practice guide of the Ministry of Public Health. The applied methodology was the observation and analysis of the data contained in the clinical history that served as a reference for the writing of the case, detailed information was sought in the Clinical Practice Guide of the Ministry of Public Health regarding the recommendations for the management of gestational diabetes, in addition to the review of bibliographic material in databases indexed in academic Google. For the diagnosis, anamnesis and physical examination were carried out, fetal macrosomia was determined by uterine height using Leopold's maneuvers, complementary tests such as ultrasound were requested. Treatment and prognosis were based on the Gestational Diabetes Clinical Practice Guide from the Ministry of Public Health. One of the main conclusions is that when there is the presence of risk factors for developing gestational diabetes, immediate action must be taken to detect or rule out said pathology; otherwise, screening should be carried out between week 24 and 28 of gestation.